Spectral mapping reveals a resemblance of the anesthetic brain state to both sleep and coma - Janna D. Helfrich; Jerzy Szaflarski; Marianne C. J. Nævra; Luis Romunstad; Matthew P. Walker; Bryce A. Mander; Robert T. Knight; Pål G. Larsson; Randolph F. Helfrich (Proceedings of the National Academy of Sciences, 2026)
General anesthesia is often compared to sleep but may more closely resemble a medically induced coma. While all three states involve a loss of awareness, the extent of their neural similarity remains unclear. Electrophysiological markers, such as delta activity (< 4 Hz), are present in slow wave sleep, disorders of consciousness (DoC, including coma), and propofol anesthesia but are absent during rapid eye movement (REM) sleep. Frontal alpha oscillations are a key feature of propofol anesthesia and detectable via intraoperative EEG. However, it remains unclear whether alpha and delta activity fully define the brain state. Using whole-head EEG, we analyzed brain activity in individuals under propofol anesthesia, during sleep, or in DoC in the intensive care unit. Our spectral parameterization and similarity analyses revealed that propofol anesthesia exhibits spatiotemporal patterns resembling both coma and sleep. We introduced a spectral orthogonalization approach, identifying unique signatures of propofol anesthesia, including posterior slow waves, frontocentral delta, and reduced aperiodic activity. Critically, the reduction in aperiodic activity partially overlaps with REM sleep and may reflect decreased cortical excitability, contributing to reduced arousal, muscle atonia, and immobility common to both states. These results imply that propofol anesthesia creates a brain state where some features resemble sleep while others are more similar to coma. Embracing its full spatiotemporal complexity could improve titration of sedation, thus minimizing excessive suppression and the risk of postoperative cognitive deficits.